Activation of mechanoreceptor Piezo1 inhibits enteric neuronal growth and migration in vitro - Moneme, Chioma; Olutoye, Oluyinka O.; Sobstel, Michał F.; Zhang, Yuwen; Zhou, Xinyu; Kaminer, Jacob L.; Hsu, Britney A.; Shen, Chengli; Mandal, Arabinda; Li, Hui; Yu, Ling; Balaji, Swathi; et al. (Frontiers in molecular neuroscience, 2024)
Dysfunction of the enteric nervous system (ENS) is linked to a myriad of gastrointestinal (GI) disorders. Piezo1 is a mechanosensitive ion channel found throughout the GI tract, but its role in the ENS is largely unknown. We hypothesize that Piezo1 plays an important role in the growth and development of the ENS. Enteric neural crest-derived progenitor cells (ENPC) were isolated from adult mouse intestine and propagated in culture as neurospheres. ENPC-derived neurons were then subject to stretch in the presence or absence of Piezo1 antagonist (GsMTx4). Transcriptomes of stretched and unstretched ENPC-derived cells were compared using bulk RNA sequencing. Enteric neurons were also cultured under static conditions in the presence of Piezo1 agonist (Yoda1) or antagonist. Neuronal phenotype, migration, and recovery from injury were compared between groups. Though stretch did not cause upregulation of Piezo1 expression in enteric neurons, both stretch and Piezo1 activation produced similar alterations in neuronal morphology. Compared to control, neurite length was significantly shorter when stretched and in the presence of Piezo1 activation. Piezo1 inhibition prevented a significant reduction in neurite length in stretched neurons. Piezo1 inhibition also led to significantly increased neuronal migration, whereas Piezo1 activation resulted in significantly decreased neuronal migration and slower neuronal recovery from injury. Mechanotransduction plays an important role in regulating normal GI function. Our results suggest that the Piezo1 mechanoreceptor may play an important role in the ENS as its activation leads to decreased neuronal growth and migration. Piezo1 could be an important target for diseases of ENS dysfunction and development.